2010
DOI: 10.1111/j.1439-0531.2008.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Follicular Fluid Fatty Acid Profiles in Dairy Cows

Abstract: Composition of follicular fluid to which the preovulatory follicle is exposed may be one of the major factors determining subsequent fertility, as fatty acids are a precursor of hormones involved in dominance, ovulation and atresia mechanisms. The objective of this paper is to observe fatty acid profiles in various lipid classes according to estrogenic activity of follicles. For each of the 18 cows, we analysed plasma and follicular fluid fatty acid profiles of phospholipids, non-esterified fatty acid (NEFA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 26 publications
1
39
3
Order By: Relevance
“…The published data are, however, quite inconsistent and mostly focused on ruminants. Renaville et al (2010) observed a positive correlation between developmental potential of bovine oocytes and higher content of C16:0 in the FF of active follicles (oestrogen to progesterone ratio -E2/P4 > 1). Homa and Brown (1992) reported no significant differences (except for C18:2) in FA composition between small (1-3 mm diameter) and large (7-13 mm) follicles.…”
Section: Fa Composition Of Ff In Relation To the Diet And Its Influenmentioning
confidence: 80%
See 1 more Smart Citation
“…The published data are, however, quite inconsistent and mostly focused on ruminants. Renaville et al (2010) observed a positive correlation between developmental potential of bovine oocytes and higher content of C16:0 in the FF of active follicles (oestrogen to progesterone ratio -E2/P4 > 1). Homa and Brown (1992) reported no significant differences (except for C18:2) in FA composition between small (1-3 mm diameter) and large (7-13 mm) follicles.…”
Section: Fa Composition Of Ff In Relation To the Diet And Its Influenmentioning
confidence: 80%
“…Wakefield et al (2008) observed an increase in PUFAs in plasma and ovaries in response to elevated n-3 PUFA concentration in diet. On the other hand, some reports show a lack of correlation between FA content in plasma and FF of dairy cows (Leroy et al, 2005;Renaville et al, 2010) and ewes (Wonnacott et al, 2010).…”
Section: Fa Composition Of Ff In Relation To the Diet And Its Influenmentioning
confidence: 99%
“…Oleic, palmitic and stearic acid were the most prevalent free fatty acids in follicular fluid from lactating cows, and were w40% of the levels in serum (Leroy et al 2005a). Free fatty acid levels may be related to follicle maturation, as follicles with higher oestrogen: progesterone (E 2 :P 4 ) ratio have more palmitic and oleic acids and less stearic and linoleic acids (Renaville et al 2010). In human follicular fluid, recent analyses have demonstrated that most serum metabolites including triacylglycerol and free fatty acids are reflected in follicular fluid, but at lower levels (Valckx et al 2012).…”
Section: Fatty Acid Supply To the Cocmentioning
confidence: 99%
“…Marei et al (2010) pointed out that linoleic acid (n-6) is the most abundant fatty acid in follicular fluid of cattle and has an important role in the regulation of the process of maturation of the ovocyte, since when the cell complex of the cumulus and ovocyte were treated with linoleic acid there was a delay in the growth of the latter. Some studies have shown the fatty acid profiles in follicular fluid are affected by the estrogenic activity of the follicle (Renaville et al, 2010). Table 4 shows saturated and unsaturated fatty acids in plasma and in some reproductive tissues.…”
Section: Lipids Their Effect On Embryo Developmentmentioning
confidence: 99%